Comparative Analysis of Arduino-microcontroller based on PWM and MPPT Solar Charge Controller for Stand-alone Solar PV System in Charging Stations of Electric Vehicles - Chan Myae Aung; Ei Mon; Than Than Htike; Hla Myo Tun (The Indonesian Institute of Science and Technology Research, 2025)
This study especially focuses on Arduino-microcontroller based pulse width modulation (PWM) and maximum power point tracking (MPPT) solar charge controller design using buck topology for stand-alone solar photovoltaic (PV) application where the PV output voltage is larger than the load/battery voltage. It consists of the design calculation for solar charge controller, design simulation techniques, construction of the hardware circuit design and modified perturb and observe (P&O) MPPT algorithm by utilizing the variable duty cycle step size. In the PWM solar charge controller design approaches, the fixed duty cycle, D=89% is specified and in the MPPT approaches, the variable duty cycle step size is applied. The design approaches with simulation techniques are also performed by professional circuit IDE (Proteus). After completing the design approaches with simulation techniques, the construction of hardware circuit for both PWM and MPPT is also conducted in the research laboratory of Yangon Technological University (YTU). In this study, the real-time measurement (RTM) technique for practical measurements and their results are offered and compared with the results on simulation techniques. The practical operation, monitoring and recording of data are also executed by using Arduino microcontroller (ATmega328P) with Arduino Data Logger Shield. The comparison results on RTM practical approaches for both PWM and MPPT solar charge controllers are given and their performance specifications are also evaluated. Both of two approaches can safely be used to charge the 12V rechargeable battery in reality. However, RTM practical results confirm that the designed MPPT controller could be improved 9% efficiency than PWM technique. Therefore, the designed MPPT solar charge controller is more efficient than PWM technique and suitable for real world applications in 12V, 100Wp stand-alone PV system.